THE LEGAL PROBLEMS OF LAND LAW TOWARD INVESTMENT ERA IN INDONESIA - Supriadi, Supriadi; Weri, Asmadi; Sari, Dewi Kemala (Tadulako Law Review, 2018)
The development of the Indonesian nation needs assistance from abroad, through the mechanism of investment, and in the context of investment in Indonesia providing facilities in the field of import duties, and land use permits. The ease of granting permits to use the land is often an obstacle, because there is a clash between the community and large companies, the government and other agencies. To avoid such conflicts, the road taken is to build awareness of all stakeholders, especially government officials and security forces. the people who own / control their land are only intended to connect their lives. Meanwhile, government officials and security forces and law enforcement officials realized that "humanity is very valuable above all. Thus the method used is three approaches (i) type of research, which are related to the type of normative research; (ii) problem approach, using, namely: (a) conceptual approach; (b) the law approach. This approach will be used as a means to conduct legal analysis of the implementation of the construction of LNG or liquefied natural gas infrastructure in Uso Batui Village, Banggai District.Â The existence of an LNG development project managed by PT Donggi Senoro LNG, in practice led to conflicts between communities related to the non-implementation of Presidential Regulation No. 36 of 2005 as the basis for implementing compensation payments. By using the research method, the issue of land acquisition for the public interest is taken by means of: (i) the apparatus, both government officials, law enforcement officials, and agencies of the National Land Agency must do the right and fair in making decisions regarding land; (ii) placing the value of justice above the interests of legislation.